TiRobot‐Assisted Percutaneous Cannulated Screw Fixation for Elderly Patients with Fragility Fractures of the Pelvis: A Retrospective Study - Baorui Xing; Xiaoyu Shen; Lijie Ma; Xiangbei Qi (Orthopaedic Surgery, 2024)
Objective The incidence of fragility fractures of the pelvis (FFPs) is increasing in the elderly population, and FFPs that require fixation are a challenge for orthopedic surgeons. The insertion of implants is not risk free due to the complex anatomical and osteoporotic bones and requires a steep learning curve. This study aimed to investigate the clinical efficacy of TiRobot‐assisted percutaneous cannulated screw fixation in the treatment of elderly FFP patients. Method The clinical data of 46 elderly FFP patients who had been treated with percutaneous cannulated screw fixation from May 2020 to September 2022 were retrospectively analyzed. Twenty‐four patients were treated with percutaneous cannulated screw fixation assisted by the TiRobot (TiRobot‐assisted group) and 22 patients were treated with conventional freehand surgery (freehand group). Postoperative outcomes, including Matta value, excellent and good rate (EGR) of fracture reduction, and accuracy of screw placement (ASP), were compared. Changes in the Visual analog scale (VAS) pain score and the Majeed score were recorded and compared between groups before and after surgery and during the 24‐week follow‐up. Repeated‐measures analysis of variance (ANOVA) and effect sizes were used as analysis methods. Results A total of 90 screws were implanted, 51 screws in the TiRobot‐assisted group and 39 screws in the freehand group. The operation time of the two groups was 34.1 ± 2.67 min versus 64.5 ± 4.19 min (p < 0.001). There were no screw‐related complications or revision surgeries in any group. The Matta value of the TiRobot‐assisted group was 5.13 ± 3.52, which was significantly lower than that of the freehand group (9.00 ± 3.68, p < 0.001), while the EGR was 91.67% versus 72.73%, with statistical significance (p < 0.001). The ASP was 100% in the TiRobot‐assisted group, better than that in the freehand group, where it was 85.7% (p = 0.043). At each timepoint in the early postoperative period, the VAS score of the TiRobot‐assisted group was significantly lower than that of the freehand group and was close to consistent by the last follow‐up; the Majeed score of the former was significantly higher than that of the latter at each timepoint of follow‐up, with statistical significance (p < 0.001). Conclusion TiRobot‐assisted percutaneous cannulated screw fixation of elderly FFP patients is advantageous over conventional freehand surgery, with less invasion, more accurate screw placement, better fracture reduction, early pain relief, and rapid recovery, suggesting that Freehand method to stabilize FFP in the elderly population.